FEMALE ENTREPRENEURSHIP DEVELOPMENT TRENDS IN KAZAKHSTAN - Zh. Smailova,; Taspenova Gaukhar, (Academic Journal of Physical and Chemical Sciences, 2019)
Today, female entrepreneurship has a special structure of business motivation, which differs from the motivation of men.This gender difference allows it possible to consider female entrepreneurship as a special type of business activity.This article discusses the female and male business styles, it is noted that the female business model is characterized by a tendency to smooth out conflicts, the ability to see all the details at once and combine several activities. There was revealed the gender motivation of women to run an entrepreneurial activity. Modern development trend analysis of female entrepreneurship in Kazakhstan has been carried out and the main barriers influencing the development of female entrepreneurship in Kazakhstan have been highlighted as well. Recommendations for further improvement of women's entrepreneurship support systems in Kazakhstan are given.